A heterogeneous catalytic alcoholysis recycling method for waste wind power blade carbon fibers

CN122913197APending Publication Date: 2026-10-16SHANGHAI UNIV OF ENG SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610933174.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]有鉴于此,本发明提供了一种用于废旧风电叶片碳纤维的异相催化醇解回收方法,以解决现有均相有机碱催化醇解体系中催化剂分散于反应介质、后处理复杂以及难以进行固液分离的问题

Benefits of technology

a) 本发明通过将TBD共价接枝于介孔硅材料表面,实现了均相有机碱催化剂的异相化;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913197A_ABST
    Figure CN122913197A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of carbon fiber recycling and the technical field of heterogeneous catalytic materials, and discloses a heterogeneous catalytic alcoholysis recycling method for waste wind turbine blade carbon fibers. First, mesoporous silica nanomaterial (MSN) is used as a carrier, and the surface thereof is functionally modified by 3-chloropropyltrimethoxysilane to prepare chloropropyl-functionalized mesoporous silica material. Then, TBD is used to covalently graft the material to obtain a TBD-MSN heterogeneous catalyst. The catalyst and an alcohol solvent are used to construct a heterogeneous catalytic alcoholysis system for recycling and processing waste wind turbine blade carbon fiber composites, which can realize effective degradation of the resin matrix and separation of the carbon fibers. The present application realizes heterogeneous catalysis of the catalyst, the catalyst can be recycled by filtration, has certain reuse potential, and provides a new technical solution for heterogeneous catalytic recycling of waste wind turbine blade carbon fiber composites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of carbon fiber recycling technology and heterogeneous catalytic materials technology, and more specifically to a heterogeneous catalytic alcoholysis recycling method for waste wind turbine blade carbon fibers. Background Technology

[0002] With the rapid development of the wind power industry, a large number of wind turbines are gradually entering the decommissioning stage, leading to an increasingly prominent problem in the disposal of waste wind turbine blades. Wind turbine blades are typically made of thermosetting resin-based fiber-reinforced composite materials, which are lightweight, high-strength, and corrosion-resistant. Among them, carbon fiber reinforced composite materials are widely used in large wind turbine blade structures due to their excellent mechanical properties. However, because thermosetting resins have an irreversible cross-linked structure, waste wind turbine blades are difficult to recycle through traditional melting and reprocessing methods. As a result, a large number of waste blades are mainly disposed of through landfill, incineration, or mechanical crushing, which not only wastes resources but also brings significant environmental pressure.

[0003] Currently, the main methods for recycling spent wind turbine blades include mechanical recycling, pyrolysis, and chemical recycling. Mechanical recycling suffers from significant fiber length loss and low added value; while pyrolysis can remove resin, the high temperatures easily lead to increased surface defects and performance degradation in carbon fibers. In contrast, chemical recycling, specifically alcoholysis, has received widespread attention in recent years due to its relatively mild reaction conditions, less fiber damage, and higher resin degradation efficiency.

[0004] In existing research, the organic base catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) is widely used in the alcoholysis degradation of thermosetting resins due to its strong basicity and high catalytic activity. For example, Chinese invention patent No. 202411801221.9 discloses a method for recycling carbon fibers. This method utilizes a homogeneous organic base / alcohol system disclosed in existing research and patents to chemically recycle composite materials, which can achieve resin matrix degradation and carbon fiber separation to a certain extent. However, existing organic base catalytic systems mostly exist in a homogeneous form in the reaction medium, and the catalyst is usually uniformly dispersed in the reaction system, making separation and recovery difficult after the reaction. Currently, there is relatively little research on the application of immobilized heterogeneous organic base catalytic systems in the alcoholysis recycling of waste wind turbine blade composite materials. Therefore, this study aims to develop a heterogeneous catalytic alcoholysis method suitable for the recycling of waste wind turbine blade carbon fiber composite materials. This method involves immobilizing the organic base catalyst on the surface of a mesoporous material to construct a heterogeneous catalytic system, enabling the catalyst to be recovered after the reaction and continue to participate in subsequent reactions. This study provides a new technical approach for the resource recycling of composite materials from waste wind turbine blades, which has certain research significance and application value. Summary of the Invention

[0005] In view of this, the present invention provides a heterogeneous catalytic alcoholysis recovery method for waste wind turbine blade carbon fibers, in order to solve the problems of catalyst dispersion in the reaction medium, complex post-processing, and difficulty in solid-liquid separation in the existing homogeneous organic base catalytic alcoholysis system.

[0006] This invention achieves catalyst heterogeneity by immobilizing an organic base catalyst on the surface of a mesoporous silica material, enabling the catalyst to participate in the alcoholysis reaction in an immobilized form. After the reaction, the catalyst can be recovered by filtration, and the recovered catalyst can still participate in subsequent alcoholysis reactions, indicating its potential for reuse. This provides a new technical solution for the heterogeneous catalytic recycling of carbon fiber composite materials from waste wind turbine blades.

[0007] A heterogeneous catalytic alcoholysis method for recycling carbon fibers from waste wind turbine blades, wherein the waste wind turbine blades are made of carbon fiber reinforced epoxy resin matrix composite material, and the method includes the following steps:

[0008] a) Mix TBD-functionalized mesoporous silica heterogeneous catalyst with an alcohol solvent to form a catalytic alcoholysis system; b) The pretreated and dried waste wind turbine blade carbon fiber composite material is added to the catalytic alcoholysis system and soaked at 160-200°C under normal pressure for 2-4 hours; alcoholysis reaction is carried out under heating conditions to degrade the resin matrix and achieve the separation and recycling of carbon fiber. c) After the reaction is completed, the heterogeneous catalyst and the recovered carbon fiber are separated by filtration, washed with deionized water 3 to 6 times, and then dried. Under normal pressure and temperature, the obtained crude carbon fiber is rinsed with acetone 3 to 4 times, then cleaned with an ultrasonic cleaner for 15 minutes, then immersed in acetone for 12 to 24 hours, and finally dried.

[0009] The TBD-functionalized mesoporous silica heterogeneous catalyst is prepared using the following method: 1) Preparation of mesoporous silica material MSN; 2) Surface functionalization modification of MSN was performed using chloropropylsilane coupling agent to obtain chloropropyl-functionalized mesoporous silicon material CPMSN; 3) 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) was covalently grafted onto the surface of CPMSN via a nucleophilic substitution reaction to obtain a TBD-functionalized mesoporous silica heterogeneous catalyst.

[0010] The chemical structure of 1,5,7-triazabicyclo[4.4.0]dec-5-ene (abbreviated as TBD, CAS number 5807-14-7) is shown below:

[0011] Furthermore, the heterogeneous catalyst needs to be dried and stored at room temperature.

[0012] Furthermore, the heterogeneous catalyst needs to be dried at 100°C for 2 hours before use.

[0013] Furthermore, the alcohol solvent includes one or more of ethylene glycol, phenylethanol, and polyethylene glycol, preferably β-phenylethanol.

[0014] Furthermore, in step b), the mass ratio of the heterogeneous catalyst to the waste wind turbine blade in the catalytic alcoholysis system is (1-4) g: 1 g.

[0015] Furthermore, in step b), the pretreatment includes surface cleaning.

[0016] Furthermore, in step b), the preprocessing also includes a cutting process.

[0017] Furthermore, in step c), the drying refers to drying at 80–100°C for 2–4 hours.

[0018] Furthermore, the carbon fiber content in the waste wind turbine blades is 25% to 85% by mass.

[0019] Furthermore, the heterogeneous catalyst can be recovered and reused by filtration after the reaction is completed.

[0020] As can be seen from the above technical solution, compared with the prior art, the present invention has at least the following significant beneficial effects: a) This invention achieves the heterogeneity of homogeneous organic base catalysts by covalently grafting TBD onto the surface of mesoporous silicon materials; b) The constructed heterogeneous catalytic system can achieve rapid separation by filtration after the reaction, reducing the difficulty of post-processing; c) The catalyst described in this invention has good potential for recycling and reuse, and the recycled catalyst still has certain catalytic activity; d) This invention enables the effective degradation of the resin matrix and the recycling of carbon fibers in waste wind turbine blade composite materials; e) This invention is applicable to the resource recycling of high fiber content waste wind turbine blade composite materials and has good engineering application value. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0022] Figure 1 The images show the heterogeneous catalyst TBD-MSN prepared in Example 3 and its recovered product. Figure 2 Fourier transform infrared spectra of the MSN, CPMSN, and TBD-MSN prepared in Examples 1, 2, and 3; Figure 3 Thermogravimetric analysis curves of MSN, CPMSN, and TBD-MSN prepared in Examples 1, 2, and 3; Figure 4 These are photographs of the morphology of waste wind turbine blades in Example 4 after soaking for different times in a heterogeneous catalytic alcoholysis system. Figure 5 These are actual photos of the carbon fiber before and after recycling in Example 4; Figure 6 The images are scanning electron microscope (SEM) images of the carbon fibers recovered in Example 4 at different magnifications, where the magnifications of images (a)-(d) are 50 μm, 20 μm, 10 μm, and 5 μm, respectively. Figure 7 The Fourier transform infrared spectrum of the catalyst after recovery in Example 4; Figure 8 Thermogravimetric analysis curve of the catalyst after recovery in Example 4; Figure 9 The images are scanning electron microscope (SEM) images of the carbon fibers recovered in Example 5 at different magnifications, where the magnifications of images (a)-(d) are 50 μm, 20 μm, 10 μm, and 5 μm, respectively. Figure 10 The images are scanning electron microscope (SEM) images of the recovered carbon fibers from Comparative Example 3 at different magnifications. The magnifications of images (a)-(d) are 50 μm, 20 μm, 10 μm, and 5 μm, respectively. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] In the following examples, the alcohol solvent used was β-phenylethanol, the waste wind turbine blades used were all carbon fiber reinforced epoxy resin composite materials, and the mass content of carbon fiber in them was 73%. The carbon fiber recovery rate was calculated according to the following formula:

[0025] In the formula: DR refers to the carbon fiber recycling rate, w2 refers to the mass of the pretreated and dried waste wind turbine blades, and w1 refers to the mass of the recycled carbon fiber after recycling treatment.

[0026] Example 1 Preparation of mesoporous silicon material MSN Mesoporous silicon material MSN was prepared using hexadecyltrimethylammonium bromide (CTAB) as a template agent and tetraethyl orthosilicate (TEOS) as a silicon source.

[0027] First, in the presence of 3.5 mL of 2 M KOH, 1 g of CTAB was added to 350 mL of deionized water and stirred at 80 °C for 1 h to allow the template agent to fully dissolve and form a stable system.

[0028] Subsequently, 5 mL of TEOS was slowly added dropwise under continuous stirring, and the reaction was continued at 80 °C for 2 h to allow the silicon source to undergo hydrolysis and condensation reaction to form a mesoporous silicon framework structure.

[0029] After the reaction was complete, the system was cooled to room temperature and filtered using a vacuum filter. The resulting product was washed several times with deionized water to remove unreacted substances and residual alkali.

[0030] The resulting product was then dried at 100°C for 24 hours.

[0031] To remove the template agent, the resulting white product was added to a mixed solution of 0.5 mL concentrated hydrochloric acid and 50 mL methanol, and the mixture was stirred at 60 °C for 6 h for template extraction.

[0032] After the reaction was completed, the product was filtered and repeatedly washed with methanol to remove excess template agent. Then it was dried at 100°C for 6 hours to finally obtain white powdered mesoporous silica material MSN.

[0033] Example 2 Preparation of Chloropropyl-functionalized mesoporous silica material CPMSN First, 2g of MSN prepared in Example 1 was dispersed in 50mL of anhydrous toluene.

[0034] Subsequently, 0.85 mL of 3-chloropropyltrimethoxysilane (3-CPTES) was added to the system and reacted under reflux at 115 °C for 24 h to allow 3-CPTES to undergo a condensation reaction with the silanol groups on the MSN surface, thereby achieving chloropropyl functionalization.

[0035] After the reaction was complete, the system was cooled to room temperature and filtered using a vacuum filter.

[0036] The product was repeatedly washed with anhydrous toluene to remove unreacted 3-CPTES and residual organic matter.

[0037] Finally, the product was dried at 100°C for 6 hours to obtain chloropropyl functionalized mesoporous silica material CPMSN.

[0038] Example 3 Preparation of TBD-functionalized mesoporous silica (TBD-MSN) heterogeneous catalysts First, 2g of the CPMSN prepared in Example 2 was pre-dried at 150°C for 2 hours to remove adsorbed moisture from the material surface.

[0039] Subsequently, the pre-dried CPMSN was dispersed in 50 mL of anhydrous toluene, and 1.04 g of TBD was added.

[0040] The reaction was carried out under reflux conditions for 8 hours, allowing TBD to be covalently grafted onto the CPMSN surface via a nucleophilic substitution reaction.

[0041] After the reaction was complete, the system was cooled to room temperature and filtered using a vacuum filter.

[0042] The product was washed with a mixed solution of toluene, methanol and deionized water in a volume ratio of 1:1:1 to remove ungrafted TBD and residual impurities.

[0043] Finally, the obtained product was dried in air for 12 hours to obtain a TBD-functionalized mesoporous silica heterogeneous catalyst.

[0044] Figure 1 These are the heterogeneous catalysts prepared and recovered in this embodiment.

[0045] Figure 2 These are the Fourier transform infrared spectra of the samples prepared in Examples 1, 2, and 3. According to the test results, a peak at 1086 cm⁻¹ can be observed in the MSN sample. -1 A distinct strong absorption peak appears at 798 cm⁻¹, corresponding to the asymmetric stretching vibration of Si-O-Si, while... -1 and 464cm -1These vibrations are attributed to the symmetric stretching and bending vibrations of Si-O-Si, respectively. In the CPMSN spectrum, the characteristic peaks of the Si-O-Si framework remain, indicating that the functionalization process did not disrupt the bulk structure of mesoporous silica. Compared to MSN, the 960 cm⁻¹ peak... -1 The characteristic peaks attributable to Si-OH in the vicinity show a significant decrease, indicating that some surface silanol groups have participated in the silanization reaction and condensed with CPTES to form Si-O-Si bonds. This shows that chloropropylsilane has been successfully grafted onto the MSN surface. After further grafting TBD, new organic characteristic absorption peaks appeared in the TBD-MSN spectrum. Among them, the peak at 1634 cm⁻¹ is particularly prominent. -1 The absorption peak at 1377 cm⁻¹ is attributed to the C=N stretching vibration, a typical characteristic peak in the TBD molecular structure; -1 The nearby absorption peaks correspond to CN bond vibrations and the characteristic absorption of nitrogen-containing ring structures, indicating that TBD has been successfully grafted onto the surface of mesoporous silicon materials.

[0046] Figure 3 These are thermogravimetric analysis (TGA) curves of the samples prepared in Examples 1, 2, and 3. Based on the test results, by comparing the weight loss difference between CPMSN and TBD-MSN in the 300–650 °C range, the actual grafting amount of TBD can be calculated to be approximately 20 wt%. Simultaneously, the TGA curves show significant weight loss for TBD-MSN within the 300–650 °C range, while the change in CPMSN is relatively gradual, further demonstrating that TBD has been successfully grafted onto the CPMSN surface, rather than through simple physical adsorption.

[0047] Example 4 The alcoholysis recycling method for waste wind turbine blade carbon fiber composite materials includes the following steps: a) At room temperature, 5 g of TBD-MSN was added to a 250 mL container, followed by 50 g of β-phenylethanol, to form a heterogeneous catalytic alcoholysis system. The TBD-MSN is a heterogeneous catalyst, prepared by covalently grafting TBD onto the surface of a mesoporous silica support. b) Immerse 1.53g of pretreated and dried waste wind turbine blades in the catalytic system prepared in step a) (73% carbon fiber content) and soak at atmospheric pressure and 190°C for 2 hours; the pretreatment refers to first cleaning the surface of the waste wind turbine blades with deionized water to remove impurities from the surface of the waste wind turbine blades, and then using a CNC cutting machine to cut the surface-cleaned waste wind turbine blades into fragments, chunks or particles of appropriate size that can be placed in a container, and then drying the fragments, chunks or particles obtained by cutting to constant weight; c) After the reaction is complete, the system is cooled to room temperature, and the solid catalyst and the recycled carbon fiber are separated by filtration. The resulting crude carbon fiber is first rinsed with acetone four times, then cleaned with an ultrasonic cleaner for 15 minutes, and finally immersed in acetone for 24 hours.

[0048] The carbon fibers were removed, washed six times with deionized water, and then dried in an oven at 100°C for 2 hours. Calculations showed that the carbon fiber recovery rate in this embodiment was 100%.

[0049] After being washed multiple times with deionized water and dried in an oven at 100°C for 2 hours, the separated TBD-MSN catalyst can be used for the next round of alcoholysis reaction.

[0050] The results show that the heterogeneous catalytic system constructed in this invention can effectively degrade the resin matrix and recycle carbon fibers in waste wind turbine blade composite materials.

[0051] Figure 4 These are photographs of the morphology of waste wind turbine blades after soaking for different times in a heterogeneous catalytic alcoholysis system.

[0052] Figure 5 These are photos of the carbon fiber before and after recycling in this embodiment.

[0053] Figure 6 These are scanning electron microscope images of the carbon fibers recovered in this embodiment at different magnifications; the carbon fibers recovered in this embodiment are of uniform thickness.

[0054] Figure 7 This is the Fourier transform infrared spectrum of the heterogeneous catalyst recovered in this example. The test results show that the recovered TBD-MSN still retains the characteristic structure of TBD and the mesoporous silica framework, indicating that this heterogeneous catalyst has a certain structural stability and recycling potential in the alcoholysis recovery system.

[0055] Figure 8 This is the thermogravimetric analysis curve of the heterogeneous catalyst recovered in this example. The test results show that the recovered TBD-MSN still retains some organic grafted structures, indicating that TBD was not completely lost and the catalyst has a certain structural stability and recycling potential. However, compared to the fresh catalyst, the weight loss of its organic components is reduced, indicating that there is a certain degree of loss of active components during the reaction process.

[0056] Example 5 The only difference between this embodiment and embodiment 4 is that the soaking temperature in step b) is replaced with "180°C" instead of "190°C". All other operations are the same as those described in embodiment 4.

[0057] Calculations show that the carbon fiber recovery rate in this embodiment is 76.24%.

[0058] Figure 9 These are scanning electron microscope images of the carbon fibers recovered in this embodiment at different magnifications; the carbon fibers recovered in this embodiment are of uniform thickness, with only a small amount of resin remaining on the surface.

[0059] Comparative Example 1 The only difference between this comparative example and Example 4 is that the heterogeneous catalyst TBD-MSN is not added in step a), and only β-phenylethanol is used for the reaction. All other operations are the same as those described in Example 4.

[0060] Experiments showed that no changes occurred when waste wind turbine blades were immersed in β-phenylethanol at atmospheric pressure and 190°C for 2 hours.

[0061] Comparative Example 2 The only difference between this comparative example and Example 4 is that the catalyst in step a) is replaced with "MSN" instead of "TBD-MSN". All other operations are the same as those described in Example 4.

[0062] Experiments showed that no changes occurred when waste wind turbine blades were immersed in the catalyst and alcohol solvent at atmospheric pressure and 190°C for 2 hours.

[0063] Example 6 The only difference between this embodiment and Embodiment 4 is that the catalyst in step a) is replaced with "recycled TBD-MSN", and all other operations are the same as those in Embodiment 4.

[0064] Experiments showed that the recovered TBD-MSN heterogeneous catalyst could still participate in the alcoholysis reaction of waste wind turbine blade composite materials. The catalyst recycling rate of resin degradation was 24.3%, indicating a certain catalytic activity and demonstrating that the constructed supported heterogeneous catalytic system has a certain degree of reusability. However, due to some catalyst loss during recovery and separation, there is still room for further optimization of its subsequent recycling performance.

[0065] Example 7 The only difference between this embodiment and embodiment 4 is that the mass of β-phenylethanol in step a) is replaced with "100g" instead of "50g". All other operations are the same as those described in embodiment 4.

[0066] Calculations show that the carbon fiber recovery rate in this embodiment is 73.3%.

[0067] Example 8 The only difference between this embodiment and embodiment 4 is that the mass of β-phenylethanol in step a) is replaced with "150g". All other operations are the same as those described in embodiment 4.

[0068] Calculations show that the carbon fiber recovery rate in this embodiment is 43.4%.

[0069] Example 9 First, this embodiment differs from Embodiment 1 in that 5 mL of TEOS is slowly added dropwise under continuous stirring, and the reaction is continued at 80°C for 1 hour to allow the silicon source to undergo a hydrolysis-condensation reaction to form a mesoporous silicon framework structure. All other operations are consistent with Embodiments 2 and 3. The actual grafting amount of TBD is calculated to be approximately 17%.

[0070] Secondly, the only difference between this embodiment and Example 4 is that the catalyst in step a) is replaced by "TBD-MSN" with "TBD-MSN prepared in this embodiment", and the rest of the operations are the same as those in Example 4.

[0071] Calculations show that the carbon fiber recovery rate in this embodiment is 83.7%.

[0072] Comparative Example 3 The only difference between this comparative example and Example 4 is that the alcohol solvent in step a) is replaced with "ethylene glycol" instead of "β-phenylethanol". All other operations are the same as those described in Example 4.

[0073] The calculated recovery rate of carbon fiber in this comparative example is 23.45%.

[0074] Figure 10 These are scanning electron microscope images of the recovered carbon fibers in this comparative example at different magnifications. The recovered carbon fibers in this comparative example have rough surfaces and numerous groove defects, and therefore clearly have no reusability.

[0075] In summary, the experimental results demonstrate that this invention, by employing MSN-supported TBD, constructs a heterogeneous catalytic alcoholysis system for the recycling of carbon fiber composite materials from spent wind turbine blades. By placing spent wind turbine blades into the constructed catalytic alcoholysis system for treatment, combined with subsequent washing and separation steps, effective degradation of the resin matrix and separation of carbon fibers can be achieved. The recovered catalyst exhibits good recycling potential and still retains certain catalytic activity.

[0076] Under specific reaction conditions, this invention enables the effective recovery of carbon fibers from waste wind turbine blades. The recovered carbon fibers exhibit significantly reduced resin residue on their surface, while maintaining their structural integrity, thus possessing further value for resource utilization. Furthermore, the method described in this invention provides a novel heterogeneous catalytic recovery technology pathway for the resource utilization of carbon fiber composite materials from waste wind turbine blades, demonstrating promising engineering applications and recycling potential, making it suitable for industrial application.

[0077] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A heterogeneous catalytic alcoholysis method for recycling carbon fiber from waste wind turbine blades, characterized in that, Includes the following steps: a) Mix TBD-functionalized mesoporous silica heterogeneous catalyst with an alcohol solvent to form a catalytic alcoholysis system; b) Add the waste wind turbine blade carbon fiber composite material to the catalytic alcoholysis system, and soak it under normal pressure and heat to carry out the alcoholysis reaction; c) After the reaction is completed, the TBD-functionalized mesoporous silica heterogeneous catalyst is recovered by solid-liquid separation, and the recovered carbon fibers are cleaned and dried.

2. The method according to claim 1, characterized in that, In step a), the TBD-functionalized mesoporous silica heterogeneous catalyst uses mesoporous silica nanomaterials as a support, and TBD is covalently grafted onto the surface of the support through a chloropropylsilane coupling agent.

3. The method according to claim 2, characterized in that, The chloropropylsilane coupling agent is 3-chloropropyltrimethoxysilane, and the actual grafting amount of TBD is 10wt% to 25wt%.

4. The method according to claim 1, characterized in that, In step a), the ratio of the TBD-functionalized mesoporous silica heterogeneous catalyst to the alcohol solvent is 1:10 to 1:40 by mass.

5. The method according to claim 1, characterized in that, In step a), the alcohol solvent is β-phenylethanol.

6. The method according to claim 1, characterized in that, In step b), the mass ratio of the TBD-functionalized mesoporous silica heterogeneous catalyst to the waste wind turbine blade is (1-4) g: 1 g.

7. The method according to claim 1, characterized in that, In step b), the carbon fiber content in the waste wind turbine blade carbon fiber composite material in the catalytic alcoholysis system is 25% to 85% by mass.

8. The method according to claim 1, characterized in that, In step b), the heating and soaking temperature is 160-200℃ and the time is 2-4 hours.

9. The method according to claim 1, characterized in that, Step b) also includes pretreatment: cleaning and cutting the surface of the waste wind turbine blade carbon fiber composite material.

10. The method according to claim 1, characterized in that, In step c), the cleaning refers to: rinsing the obtained recycled carbon fiber with acetone 3 to 4 times, then cleaning it with an ultrasonic cleaner for 15 minutes, and finally immersing it in acetone for 12 to 24 hours; the drying refers to drying at 60 to 100°C for 2 to 4 hours.

Citation Information

Patent Citations

  • Method for recycling carbon fibers in waste wind power blades

    CN120737424A